X-linked severe combined immunodeficiency. Graft-versus-host disease due to maternal engraftment. - Ibler, K.; Agner, T.; Nielsen, P.L.; Jemec, G.B.E. (European Journal of Pediatric Dermatology, 2009)
A 4-year-old boy presented severe dermatitis with recurrent infections. The histological examination showed vacuolization of the basal cells and inflammation of the dermal epidermal junction. Laboratory examinations led to diagnose severe combined immunodeficiency and the dermatitis was attributed to a graft-versus-host reaction due to maternal engraftment. The skin lesions regressed 4 months after allogenic bone marrow transplantation.